Synthesis of sphere-like-crystal CdS powder and thin films using chemical residue in chemical bath deposition (CBD) for thin film solar cell application - Ali A.M.; Yusoff Y.; Ali L.M.; Misran H.; Akhtaruzzaman M.; Alghoul M.A.; Sopian K.; Radiman S.; Amin N. (Elsevier Ltd, 2023)
Cadmium sulfide; Cadmium sulfide solar cells; Cadmium telluride; Deposition; Energy gap; II-VI semiconductors; Optical properties; Solar cells; Substrates; Sulfur compounds; Thermal evaporation; Thin film solar cells; Chemical residues; Chemical-bath deposition; CIGS thin films; Glass substrates; High transmittance; Optical band gap energy; Residue; Structural and optical properties; Thin films; chemical compound; crystal structure; film; fuel cell; optical property; recycling; substrate